2021
DOI: 10.1021/acsptsci.1c00161
|View full text |Cite
|
Sign up to set email alerts
|

Xanthohumol Pyrazole Derivative Improves Diet-Induced Obesity and Induces Energy Expenditure in High-Fat Diet-Fed Mice

Abstract: The energy intake exceeding energy expenditure (EE) results in a positive energy balance, leading to storage of excess energy and weight gain. Here, we investigate the potential of a newly synthesized compound as an inducer of EE for the management of diet-induced obesity and insulin resistance. Xanthohumol (XN), a prenylated flavonoid from hops, was used as a precursor for the synthesis of a pyrazole derivative tested for its properties on high-fat diet (HFD)-induced metabolic impairments. In a comparative st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…In recent years, studies have shown that the intestinal microbiota plays an important role in the development and regulation of obesity 4 , 5 . Researchers in China and around the world have used high-fat and high-sugar methods to establish mouse models of obesity and have successfully carried out a number of studies on this basis 5 7 . However, there have been few studies on mouse models of obesity induced by intestinal microbiota dysbiosis.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, studies have shown that the intestinal microbiota plays an important role in the development and regulation of obesity 4 , 5 . Researchers in China and around the world have used high-fat and high-sugar methods to establish mouse models of obesity and have successfully carried out a number of studies on this basis 5 7 . However, there have been few studies on mouse models of obesity induced by intestinal microbiota dysbiosis.…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating studies indicate these prenylated flavonoids may mediate their beneficial effects via polypharmacological mechanisms of action, which could increase their effectiveness in treating disease. Previous studies link the anti-obesity and MetS benefits of XN and its derivatives to possibly increasing energy expenditure through mild mitochondrial uncoupling and increasing locomotor activity [ 13 , 35 , 36 ]. XN improves diet-induced obesity and hepatosteatosis by inhibiting expression of and inactivating maturation of sterol regulatory element-binding proteins, thus reducing the expression of genes involved in fatty acid and cholesterol biosynthesis [ 14 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating studies indicate these prenylated flavonoids may mediate their beneficial effects via polypharmacological mechanisms of action, which could increase their effectiveness in treating disease. Previous studies link the anti-obesity and MetS benefits of XN and its derivatives to possibly increasing energy expenditure through mild mitochondrial uncoupling and increasing locomotor activity [43, 48, 49]. Xanthohumol improves diet-induced obesity and hepatosteatosis by inhibiting expression of and inactivating maturation of sterol regulatory element-binding proteins, thus reducing the expression of genes involved in fatty acid and cholesterol biosynthesis [14, 50].…”
Section: Discussionmentioning
confidence: 99%